Aluminum and aluminum alloy hard anodic oxidation coloring process method
By micro-expanding the hard anodized film, the porosity is improved, and the problems of uneven coloring and poor binding force caused by low porosity on the surface of aluminum alloy are solved, and a hard anodized coloring film without floral and falling off are achieved, meeting product performance requirements and reducing production costs.
Patent Information
- Application Number
- CN202411552913.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-28
AI Technical Summary
The surface porosity of aluminum alloy after hard anodization is low, which makes it difficult to enter the colorant, resulting in problems such as floral surface, poor binding force, uneven coloring and light color.
By micro-porousing the hard anodized film by using anodizing process under specific conditions, the porosity of the outer layer of the oxide film is improved and the firm adhesion of the colored film is ensured.
It realizes a hard anodized coloring film without floral and shedding, with a strong bonding force, meeting product performance requirements and reducing production costs.
Smart Images

Figure CN119530922A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a coloring process for aluminum and aluminum alloys, and in particular to a hard anodizing coloring process for aluminum and aluminum alloys. Background Art
[0002] Aluminum anodizing refers to the process of forming an oxide film on the surface of aluminum or aluminum alloy in an electrolyte under certain process conditions; hard anodizing technology is the most excellent technology among all aluminum alloy surface treatment technologies. It has significant advantages such as high film thickness, high hardness and high wear resistance, and has been widely used in the surface treatment of aluminum alloys.
[0003] When the porosity of the aluminum alloy surface after hard anodizing is at a low level of ≤6%, due to the relatively small number of pores, the channels for the colorant to enter are limited. Direct coloring can easily cause surface floweriness, poor bonding strength, and shedding of the coloring film, resulting in uneven coloring and lighter color. Summary of the invention
[0004] The purpose of the present invention is to provide a hard anodizing coloring process method for aluminum and aluminum alloys in view of the deficiencies in the prior art. The method utilizes the dissolution-film-forming characteristics of aluminum and aluminum alloys in dilute sulfuric acid solution anodizing, and micro-expands the hard anodized film by using an anodizing process under specific conditions, so that the inner layer of the oxide film is dense, the porosity of the oxide film on the outer surface is improved, and the coloring bonding force of the oxide film layer is ensured to be firm without defects such as shedding and floweriness, so as to provide a hard anodized coloring film that meets the product performance requirements for aluminum alloy parts used in marine and terrestrial dual-use products.
[0005] The invention is mainly to achieve the above-mentioned purpose, and the technical solution of the invention is: Aluminum and aluminum alloy hard anodizing coloring process method comprises the following steps: 1) Pre-treatment Chemically degrease, clean, pickle and wash aluminum and aluminum alloy parts; 2) Hard anodizing Immerse the aluminum and aluminum alloy parts pre-treated in step 1) in a sulfuric acid electrolyte, energize for oxidation, and stir with air to ensure uniformity of temperature and concentration of the sulfuric acid electrolyte; 3) First rinse Immerse the aluminum and aluminum alloy parts hard anodized in step 2) in running water for rinsing; 4) Hole expansion Immerse the aluminum and aluminum alloy parts rinsed for the first time in step 3) in a sulfuric acid electrolyte, energize for oxidation expansion, and stir with air to ensure uniformity of temperature and concentration of the sulfuric acid electrolyte; 5) Second rinse Immerse the aluminum and aluminum alloy parts expanded in step 4) in running water for rinsing; 6) Coloring The aluminum and aluminum alloy parts rinsed for the second time in step 5) are immersed in a coloring liquid for coloring; 7) Third rinse Immerse the aluminum and aluminum alloy parts colored in step 6) in running water and rinse; 8) Sealing The aluminum and aluminum alloy parts rinsed for the third time in step 7) are immersed in hot pure water to seal the pores to obtain colored aluminum and aluminum alloy hard anodized parts.
[0006] Preferably, the chemical degreasing in step 1) uses an aluminum alloy descaling agent with a free alkalinity of 150 to 250 points, and the aluminum and aluminum alloy parts are immersed in the descaling agent at room temperature for 2 to 5 minutes.
[0007] Preferably, the chemical degreasing in step 1) uses a mixed solution of sodium hydroxide and sodium carbonate, wherein each liter of the mixed solution is prepared by dissolving 50 to 70 g of sodium hydroxide (industrial grade) and 30 to 70 g of sodium carbonate (industrial grade) in an appropriate amount of water, and the aluminum and aluminum alloy parts are immersed in the mixed solution at 60 to 70° C. for 1 to 3 minutes.
[0008] Preferably, the pickling in step 1) uses 200-300 g / L nitric acid (industrial grade), and the aluminum and aluminum alloy parts are immersed in the nitric acid solution at room temperature for 1-3 minutes.
[0009] Preferably, the cleaning in step 1) is performed by first immersing the aluminum and aluminum alloy parts in running water at ≥ 60° C. for 1 to 3 minutes, and then immersing the aluminum and aluminum alloy parts in running water at room temperature for 1 to 3 minutes.
[0010] Preferably, in step 2), the temperature of the sulfuric acid electrolyte is -2 to 2°C, the mass percentage concentration of the sulfuric acid electrolyte is 330 to 360 g / L, the oxidation is conducted for 30 to 40 min, and the initial current density is 0.5 A / dm 2 , the current density increases by 0.5A / dm every 5min 2 , until it rises to 3A / dm 2 ; The air stirring uses compressed air, the compressed air pressure is 0.4-0.6MPa, and the compressed air flow rate is 44-46m 3 / h.
[0011] Preferably, in step 4), the temperature of the sulfuric acid electrolyte is 4-25°C, the mass percentage concentration of the sulfuric acid electrolyte is 180-220 g / L, the oxidation expansion is carried out for 10-15 min, and the current density is 1-3 A / dm 2 ; The air stirring uses compressed air, the compressed air pressure is 0.4-0.6MPa, and the compressed air flow rate is 44-46m 3 / h.
[0012] Preferably, the rinsing in step 3), step 5) and step 7) are all multiple rinses, and a different water tank is replaced for each rinse to reduce the residual acid on the surface of the parts, and the rinsing time for each rinse is 0.5 to 1 minute; the first rinse in step 3) is rinsed twice, the second rinse in step 5) is rinsed three times, and the third rinse in step 7) is rinsed three times.
[0013] Preferably, in step 6), the temperature of the coloring liquid is 30-60° C., the pH value is 5-6, and the coloring time is 5-30 min.
[0014] Preferably, in step 8), the temperature of the hot pure water is greater than 90° C., and the immersion time is 10 to 20 minutes.
[0015] The present invention has the following advantages over the prior art: The present invention adopts an anodic oxidation process to microscopically expand the pores of a hard anodized film with a low porosity, thereby increasing the porosity of the oxide film on the outer surface. The present invention can make the aluminum and aluminum alloy parts with a porosity of 2-6% after hard anodization before expansion have no blooming or shedding of the oxide film layer after expansion and coloring, and have a strong bonding force.
[0016] Industrial sulfuric acid is used to expand the holes of aluminum and aluminum alloy after hard anodizing. The production cost is low, the bath liquid has only one component, the preparation is simple, the solution is stable, and the operation is convenient.
[0017] Applicant's experimental verification: 1. The present invention performs microscopic pore expansion on a hard anodized film with low porosity through an anodizing process, thereby meeting the performance requirement that the hardness of the hard anodized film layer is ≥300HV0.01.
[0018] 2. The method of the present invention is used to color aluminum and aluminum alloy parts. No rust appears on the surface of the aluminum and aluminum alloy parts after 2500 hours of salt spray test, which meets the requirement of no corrosion products after 192 hours of neutral salt spray test.
[0019] 3. The method of the present invention is used to color aluminum and aluminum alloy parts. Tests have shown that the colored film layer of the aluminum and aluminum alloy parts does not bloom or fall off, and meets the requirements of the adhesion strength test.
[0020] 4. The method of the present invention is used to color aluminum and aluminum alloy parts, and the coloring film layer of the aluminum and aluminum alloy parts has no defects such as blooming and falling off, and meets the agreed color. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention is a process flow chart of the method. Specific embodiments
[0022] The present invention is further described below, but the present invention is not limited to the described embodiments. Reagents:
[0023] 1. The coloring liquid is prepared by adding 5-20 g of black dye RLF-9050 and 1-3 ml of mildew preventer RLF-9060 to each liter of water and mixing evenly. The black dye and mildew preventer are purchased from Chongqing Xinren Technology Co., Ltd. 2. Aluminum alloy deoxidizing agent RLQ-132 was purchased from Chongqing Xinren Technology Co., Ltd.; 3. Other reagents were of commercial analytical grade.
[0024] Example 1 See Figure 1 Check whether the anodizing hanger is conductive and clamp the parts on the hanger. If it is difficult to clamp, use pure aluminum wire with a diameter of 3 to 5 mm to tie the aluminum and aluminum alloy parts to the hanger. The hangers are all hangers with parts clamped on them. Pretreatment: Use aluminum alloy descaling agent RLQ-132, whose free alkalinity (points) is 150-250 points, lift the hanger after hanging it in 2-5 minutes; lift the hanger after hanging it in running water ≥60℃ for 1-3 minutes, lift the hanger after hanging it in running water at room temperature for 1-3 minutes; lift the hanger after hanging it in 200-300g / L nitric acid solution at room temperature for 1-3 minutes; lift the hanger after hanging it in running water ≥60℃ for 1-3 minutes, lift the hanger after hanging it in running water at room temperature for 1-3 minutes; Hard anodizing: Place the hanger in sulfuric acid electrolyte, the temperature of the sulfuric acid electrolyte is -2 to 2°C, the mass percentage concentration of the sulfuric acid electrolyte is 330 to 360 g / L, and the oxidation is energized for 30 to 40 minutes. The initial current density is 0.5 A / dm 2 , increase by 0.5A / dm every 5 minutes 2 , until it rises to 3A / dm 2 During the power-on period, air stirring is used, the compressed air pressure is 0.4-0.6MPa, and the compressed air flow rate is 44-46m 3 / h, lift the hanger after oxidation is completed; First rinse: Hang the hanger into running water, shake it gently, rinse it twice in different running water tanks, each rinsing time is 0.5 to 1 minute, lift the hanger after rinsing; Hole expansion: Hang the hanger into sulfuric acid electrolyte, the temperature of sulfuric acid electrolyte is 4-25℃, the mass percentage concentration of sulfuric acid electrolyte is 180-220g / L, and oxidize and expand the hole for 10-15min with a current density of 1-3A / dm 2 During the power-on period, air stirring is used, the compressed air pressure is 0.4-0.6MPa, and the compressed air flow rate is 44-46m 3 / h, lift the hanger after oxidation is completed; Second rinse: Hang the hanger in running water, shake it gently, rinse it three times in different running water tanks, each rinsing time is 0.5 to 1 minute, lift the hanger after rinsing; Coloring: At a temperature of 30-60℃, place the hanger in a coloring liquid with a pH value of 5-6 and color for 5-30 minutes. During the coloring period, gently shake the hanger up and down to ensure uniform coloring. After coloring is completed, lift the hanger; Third rinse: Hang the hanger in running water, shake it gently, rinse it three times in different running water tanks, each rinsing time is 0.5 to 1 minute, lift the hanger after rinsing; Sealing: Place the hanger in hot pure water with a temperature greater than 90°C for 10 to 20 minutes. During the sealing period, gently shake the hanger up and down, lift the hanger, and the sealing is completed to obtain colored aluminum and aluminum alloy hard anodized parts.
[0025] Example 2 See Figure 1 Check whether the anodizing hanger is conductive and clamp the parts on the hanger. If it is difficult to clamp, use pure aluminum wire with a diameter of 3 to 5 mm to tie the aluminum and aluminum alloy parts to the hanger. The hangers are all hangers with parts clamped on them. Pretreatment: Use a mixed solution of sodium hydroxide and sodium carbonate, each liter of the mixed solution is prepared by dissolving 50-70g of sodium hydroxide (industrial grade) and 30-70g of sodium carbonate (industrial grade) in an appropriate amount of water. Lift the hanger at 60-70°C for 1-3 minutes; lift the hanger after lifting it after lifting it in running water ≥60°C for 1-3 minutes; lift the hanger after lifting it in running water at room temperature for 1-3 minutes; lift the hanger after lifting it in 200-300g / L nitric acid solution at room temperature for 1-3 minutes; lift the hanger after lifting it after lifting it in running water ≥60°C for 1-3 minutes; lift the hanger after lifting it in running water at room temperature for 1-3 minutes; Hard anodizing: Place the hanger in a sulfuric acid electrolyte with an electrolyte temperature of -2 to 2°C and a sulfuric acid electrolyte mass percentage concentration of 330 to 360 g / L. Apply electricity for oxidation for 30 to 40 minutes with an initial current density of 0.5 A / dm 2 , increase by 0.5A / dm every 5 minutes2 , until it rises to 3A / dm 2 During the power-on period, air stirring is used, the compressed air pressure is 0.4-0.6MPa, and the compressed air flow rate is 44-46m 3 / h, lift the hanger after oxidation is completed; First rinse: Hang the hanger into running water, shake it gently, rinse it twice in different running water tanks, each rinsing time is 0.5 to 1 minute, lift the hanger after rinsing; Hole expansion: Hang the hanger into sulfuric acid electrolyte, the electrolyte temperature is 4-25℃, the mass percentage concentration of sulfuric acid electrolyte is 180-220g / L, and oxidize and expand the hole for 10-15min with a current density of 1-3A / dm 2 During the power-on period, air stirring is used, the compressed air pressure is 0.4-0.6MPa, and the compressed air flow rate is 44-46m 3 / h, lift the hanger after oxidation is completed; Second rinse: Hang the hanger in running water, shake it gently, rinse it three times in different running water tanks, each rinsing time is 0.5 to 1 minute, lift the hanger after rinsing; Coloring: At a temperature of 30-60℃, place the hanger in a coloring liquid with a pH value of 5-6 and color for 5-30 minutes. During the coloring period, gently shake the hanger up and down to ensure uniform coloring. After coloring is completed, lift the hanger; Third rinse: Hang the hanger in running water, shake it gently, rinse it three times in different running water tanks, each rinsing time is 0.5 to 1 minute, lift the hanger after rinsing; Sealing: Place the hanger in hot pure water with a temperature greater than 90°C for 10 to 20 minutes. During the sealing period, gently shake the hanger up and down, lift the hanger, and the sealing is completed to obtain colored aluminum and aluminum alloy hard anodized parts.
[0026] Table 1 Oxide film thickness and oxide film hardness of hard anodized aluminum parts samples before and after hole expansion in the embodiment
[0027] The oxide film thickness in Table 1 is tested according to GB / T4957-2003, and the oxide film hardness is tested according to GB / T4340.1-2009. It can be seen from Table 1 that the method described in the present invention is used to hard-anodize aluminum and aluminum alloy parts and then anodize and expand the holes. The oxide film hardness of the aluminum part sample after expansion is greater than 300HV0.01, which meets the GB / T19822-2018 hard anodized film hardness ≥300HV0.01 index.
[0028] Table 2 Corrosion resistance of colored aluminum and aluminum alloy hard anodized parts samples in the embodiment
[0029] Table 2 The corrosion resistance is tested according to GB / T10125-2021. It can be seen from Table 2 that the colored aluminum and aluminum alloy hard anodized parts samples of the present invention have no rust on the surface after 2500 hours of salt spray test, meeting the requirement of no corrosion products in the neutral salt spray test for 192 hours.
[0030] Table 3 Adhesion strength of colored aluminum and aluminum alloy hard anodized parts samples in the embodiment
[0031] The coloring adhesion strength in Table 3 was tested according to WJ2607-2003. It can be seen from Table 3 that the colored aluminum and aluminum alloy hard anodized parts samples of the present invention were wiped back and forth five times on the treated film layer using a wiping method with soft cotton fabric or filter paper. After the test, the colored film layer did not show any blooming or falling off, and the adhesion strength test requirements were met.
[0032] The coloring adhesion strength of the prepared samples was tested according to GB / T5270-2005 (2.4 peeling test: tape test). After the colored aluminum and aluminum alloy hard anodized parts samples of the present invention were tested, the colored film layer did not fall off, and the adhesion strength test requirements were met.
[0033] The appearance of the samples was tested according to GB / T12967.6-2008. Under the specified observation conditions, the samples of the colored aluminum and aluminum alloy hard anodized parts of the present invention had no defects such as blooming and falling off, and met the agreed color.
Claims
1. A method for hard anodizing and coloring aluminum and aluminum alloys, characterized in that: The method comprises the following steps: 1) Pre-treatment Chemically degrease, clean, pickle and wash aluminum and aluminum alloy parts; 2) Hard anodizing Immerse the aluminum and aluminum alloy parts pre-treated in step 1) in a sulfuric acid electrolyte, oxidize with electricity, and stir with air; 3) First rinse Immerse the aluminum and aluminum alloy parts hard anodized in step 2) in running water for rinsing; 4) Hole expansion Immerse the aluminum and aluminum alloy parts rinsed for the first time in a sulfuric acid electrolyte, energize and oxidize to expand the holes, and stir with air; 5) Second rinse Immerse the aluminum and aluminum alloy parts expanded in step 4) in running water for rinsing; 6) Coloring The aluminum and aluminum alloy parts rinsed for the second time in step 5) are immersed in a coloring liquid for coloring; 7) Third rinse Immerse the aluminum and aluminum alloy parts colored in step 6) in running water and rinse; 8) Sealing The aluminum and aluminum alloy parts rinsed for the third time in step 7) are immersed in hot pure water to seal the pores to obtain colored aluminum and aluminum alloy hard anodized parts.
2. The coloring method according to claim 1, characterized in that Step 1) The chemical degreasing uses an aluminum alloy descaling agent with a free alkalinity of 150 to 250 points, and the aluminum and aluminum alloy parts are immersed in the descaling agent at room temperature for 2 to 5 minutes.
3. The coloring method according to claim 1, characterized in that Step 1) The chemical degreasing uses a mixed solution of sodium hydroxide and sodium carbonate. Each liter of the mixed solution is prepared by dissolving 50-70g of sodium hydroxide and 30-70g of sodium carbonate in an appropriate amount of water. The aluminum and aluminum alloy parts are immersed in the mixed solution at 60-70°C for 1-3 minutes.
4. The coloring method according to claim 1, characterized in that Step 1) The pickling is performed using 200-300 g / L nitric acid, and the aluminum and aluminum alloy parts are immersed in the nitric acid solution at room temperature for 1-3 minutes.
5. The coloring method according to claim 1, characterized in that: Step 1) The cleaning is performed by first immersing the aluminum and aluminum alloy parts in running water at ≥ 60°C for 1 to 3 minutes, and then immersing the aluminum and aluminum alloy parts in running water at room temperature for 1 to 3 minutes.
6. The coloring method according to claim 1, characterized in that: Step 2) The temperature of the sulfuric acid electrolyte is -2 to 2°C, the mass percentage concentration of the sulfuric acid electrolyte is 330 to 360 g / L, the oxidation is conducted for 30 to 40 min, and the initial current density is 0.5 A / dm 2 , the current density increases by 0.5A / dm every 5min 2 , until it rises to 3A / dm 2 ; The air stirring uses compressed air, the compressed air pressure is 0.4-0.6MPa, and the compressed air flow rate is 44-46m 3 / h.
7. The coloring method according to claim 1, characterized in that: Step 4) The temperature of the sulfuric acid electrolyte is 4-25°C, the mass percentage concentration of the sulfuric acid electrolyte is 180-220 g / L, the oxidation expansion is carried out for 10-15 min, and the current density is 1-3 A / dm 2 ; The air stirring uses compressed air, the compressed air pressure is 0.4-0.6MPa, and the compressed air flow rate is 44-46m 3 / h.
8. The coloring method according to claim 1, characterized in that: The rinsing in step 3), step 5) and step 7) are multiple rinsings, and each rinsing time is 0.5 to 1 minute.
9. The coloring method according to claim 1, characterized in that: Step 6) The coloring liquid temperature is 30-60°C, the pH value is 5-6, and the coloring time is 5-30 minutes.
10. The coloring method according to claim 1, characterized in that: Step 8) The temperature of the hot pure water is greater than 90° C., and the immersion time is 10 to 20 minutes.